Enhancing the teaching and learning of mathematics in the Senior Cycle - Flannery, David (Trinity College (Dublin, Ireland). School of Education, 2006)
This thesis aserts that the current provision of mathematics education at Senior Cycle suffers from a number of shortcomings. These are described as a failure to show the relevance of the material being taught and an almost total neglect of the history and culture of the subject along with an ignoring of its recreational element. It is contended that the reason the current programme is not having its ambitions realised effectively is due to an overly narrow interpretation of the course material by way of texts and examinations. These points are substantiated at a number of junctures throughout the dissertation but in particular, in relation to examinations, in the chapter “Establishing the Case”. It is also maintained that there is a lack of substance/rationale in the current presentation of syllabus segments and a scant use of technology; claims which are subsequently established.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin